(untitled) (Asia Pacific Journal of Social Innovation, 2022)
This is a descriptive study which aims to identify the vowels that occur, and the segmental phonotactic constraints of vowels, in disyllabic words of Tagabawa language. Analysis is based on the responses elicited from ten (10) Tagabawa native speakers, with ages 42-86 years old, at the Old Bulatukan, Makilala, Cotabato. During the interview, respondents have to provide the Tagabawa equivalents of one hundred (100) words based from Swadesh list written on flash cards, to determine the vowels and the segmental phonotactics of vowels in disyllabic words of Tagabawa. The analyses revealed that the vowel sounds in Tagabawa language: a [a], é [e] or [ɛ], á [ə], i [i], ó [ɔ], and u [u] occur only in medial and final positions in disyllabic words. The vowel sound [a] occurred in CVC/CV, CVC/CVC and CV/CVC syllable patterns; the vowel sound [ɛ] in CVC/CVC and CVC/CV syllable patterns; the vowel sound [e] in CV/CVC and CVC/CV syllable patterns; the vowel sound [ə] in CVC/CVC, CV/CVC and CVC/CV syllable patterns; the vowel sound [i] in CV/CVC and CVC/CVC syllable patterns; the vowel sound [ɔ] in CVC/CVC, CV/CVC and CVC/CV syllable patterns; and the vowel sound [u] in CV/CVC and CVC/CVC syllable patterns. The study recommends other studies of Tagabawa language because of the need to help educational institutions to develop materials using local languages, help in the promotion of the local language, and to fill the dearth of resources about the language.